PENGARUH JANGKAU SUDUT UKUR PADA HASIL ANALISIS DATA DIFRAKSI SINAR-X MENGGUNAKAN METODE RIETVELD: KASUS CAMPURAN MgO-Y2O3 (Makara Journal of Science, 2008)
Selection of Diffraction Measurement Range and Its Effect on X-ray Diffraction Rietveld Analysis Results: a MgO-Y2O3 Mixture Case. X-ray diffraction data analyses for a MgO-Y2O3 (30% Y2O3 by weight) ceramic composite have been done at various diffraction angle ranges to evaluate the effects to the analyses results. The study was performed as choosing the angle ranges correlates to data collection time and x-ray tube lasting. The analyses utilised Rietveld-based software Rietica. The ranges chosen were (A) 10-100, (B) 10-90, (C) 10-80, (D) 10-70 dan (E) 10-60 °2θ. Results showed that in general the errors of the refined parameters increased with narrower range. Phase composition analyses also showed significant bias when narrower range was used – with range 10-80 °2θ gave tolerable result. Moreover, narrowing diffraction angle in the analysis significantly biases the Lorentzian peak broadening component values particularly for phase with crystallite size estimate more than 100 nm. The study recommends how to choose the range.